(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Analysis of several climatic factors (temperature, humidity, rainfall) related to the prevalence of common infectious diseases in 2 provinces Bac Giang and Cao Bang (2014-2023). Research methods: Secondary data analysis and correlational research. Results: Some common diseases found in both provinces include influenza, diarrhea, dysentery (Shigella), amoebic dysentery, mumps, and chickenpox; Dengue fever and hepatitis B in Bac Giang; Adenovirus infections in Cao Bang. In Bac Giang, a positive moderate correlation was found between hand-foot-mouth disease and temperature and rainfall: (r = 0.422; p < 0.001); (r = 0.328; p < 0.001); mumps and diarrhea with humidity: (r = 0.336; p < 0.001); (r = 0.349; p < 0.001) and a negative correlation between chickenpox and rainfall (r = -0.304; p = 0.001). In Cao Bang, diarrhea and hepatitis B showed a positive moderate correlation with temperature: (r = 0.388; p < 0.001); (r = 0.32; p = 0.001) and chickenpox was negatively correlated with humidity (r = -0.323; p = 0.001). Conclusions: Identify the correlation of several climatic factors (temperature, humidity, rainfall) with common diseases, with this correlation being more evident in Bac Giang for diseases such as hand foot and mouth disease, mumps, diarrhea, and chickenpox, and in Cao Bang for chickenpox.